Changing minds the art and science of changing our own and other people?s minds - Gardner, Howard (Boston, Mass Harvard Business School Press, 2004)
Think about the last time you tried to change someone?s mind about something important: a voter?s political beliefs; a customer?s favorite brand; a spouse?s decorating taste. Chances are you weren?t successful in shifting that person?s beliefs in any way. In his book, Changing Minds, Harvard psychologist Howard Gardner explains what happens during the course of changing a mind ? and offers ways to influence that process.
Includes bibliographical references and index.
Keywords: Change (Psychology)